Grassroots Advocacy and Health Care Reform - Stier, M. author. aut Link
XVIII, 250 p.
Keywords: Grassroots Advocacy and Health Care Reform places a detailed account of how the Health Care for America Now campaign in Pennsylvania carried out contemporary issue advocacy in the context of an understanding of American politics.